Local Wisdom in the Kenduri Tradition among Javanese and Malay Communities in Asahan Regency: An Islamic Communication Philosophy Perspective - Lakum Lakum; Susi Lestari Siregar; Uky Firmansyah Rahman Hakim (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The Kenduri tradition is an annual cultural practice observed by the Javanese and Malay communities. This tradition embodies significant cultural and religious values. The purpose of this study is to analyze the Kenduri tradition in Asahan Regency from the perspective of Islamic communication philosophy by applying the theory of communication principles. This study employed a qualitative method with a case study approach. Data were collected through interviews and documentation. The findings reveal that the Kenduri tradition in Bumiharjo Village reflects Islamic communication values, particularly the principle of qaulan layyinan (gentle and respectful speech). The tradition is practiced in a polite and courteous manner, where community members respect and appreciate one another. In addition, the Kenduri tradition is conducted modestly and without extravagance. The implementation of this tradition is also aligned with Islamic religious norms and values. Furthermore, the Kenduri tradition is practiced honestly and fairly within the community in Asahan Regency. Based on the findings, the Kenduri tradition can serve as a medium for conveying Islamic messages to society. This tradition also contributes to increasing public awareness of Islamic values and fostering noble moral character within the community.